Correlation between Food Consumption Frequency, Protein Intake, and Micronutrients with Anemia in Young Girls at SMAN 2 Tambun Selatan. - Salma, Annisa Nabila; Andriani, Eka; Sabrina, Sabrina (Fakultas Kedokteran, 2023)
The term anemia refers to a condition when the number of red blood cells or erythrocytes in the body is insufficient to meet a person's physiological needs. Diet, infection, and genetics are some of the multifactors that contribute to the pathogenesis of anemia. Hemoglobin levels are influenced by dietary intake and the type of food consumed by a person. This study aims to determine the relationship of food consumption frequency and intake to anemia. This type of research is analytic observational research with cross sectional design. The research was conducted at SMAN 2 Tambun Selatan with a sample of 147 respondents taken using simple random sampling. Data analysis used gamma test. The results showed that there was a significant relationship between the frequency of food consumption of heme iron (p-value = 0.001) and vitamin B12 (p-value = 0.022). The frequency of consumption of other foods such as non-heme iron, iron inhibitors, folic acid, and vitamin C had no relationship or p-value >0.05. In the food intake variable, there was a relationship, namely protein intake (p-value = 0.015), iron (p-value = 0.004), and folic acid (p-value = 0.004). Dietary intake of vitamin B12 and vitamin C had no association or p-value >0.05. The conclusion in this study is that the frequency of food consumption that has a relationship is only heme iron and vitamin B12. The intake that is related is the intake of protein, iron, folic acid.